Pelatihan Pembukuan Sederhana bagi Pelaku UMKM di Desa Doda Bahari Kecamatan Sangia Wambulu Kabupaten Buton Tengah - HUS HUSRIAH; Murni Sari; Yunarsi Yunarsi; Wilda Fatmala; Filasti Rahma; Wa Ode Arnia (Universitas Pendidikan Muhammadiyah Sorong, 2022)
Good fund management is a key factor that can lead to the success or failure of UMKM. A practical and effective method in managing funds for UMKM is to apply good accounting. Thus, accounting makes UMKM able to obtain various financial information in running their business. Accounting records must be in accordance with every transaction that occurs and based on applicable accounting standards. Based on the problems above, the service team views it as very urgent to conduct simple financial recording training. Financial recording training that will be carried out for UMKM will be a solution in solving these problems. The method used from this service is the Technical method or Field work. Technical, namely simple bookkeeping training for UMKM actors in Doda Bahari Village. The results of community service show that this simple bookkeeping training is very important for MSME actors to make it easier to see the profit and loss of a business.